Entropy Generation in C6H9NAO7 Fluid Over an Accelerated Heated Plate - Ahmed, Tarek Nabil; Khan, Ilyas (Frontiers in Physics, 2020)
This study considers sodium-alginate (C6H9NaO7) fluid over an accelerated vertical plate. The plate is heated from the bottom. A non-Newtonian model of C6H9NaO7 is considered. The convection term in the momentum equations is also considered. The dimensionless form of the problem is constructed based on dimensionless variables. The integral transformation of Laplace is used to develop the exact solution to the problem. Explicit expressions are obtained for the velocity field and temperature distribution. The corresponding skin-friction and Nusselt number results are computed based on this. Equations for entropy generation (EG) and Bejan number (BN) are developed. The results are plotted and discussed for embedded parameters. Most significantly, the results for EG and BN are computed and discussed.